LIBERALISME DALAM TUBUH PENDIDIKAN ISLAM: MELACAK AKAR HISTORIS, PERANAN, SERTA DAMPAKNYA BAGI PENDIDIKAN - UMI SEPTINA ANGGRAHENI; ABID NURHUDA; ALI ANHAR SYI’BUL HUDA; DENA SRI ANUGRAH; MUHAMMAD AL FAJRI (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2026)
The background of this research is the unrest that occurs in the Islamic education system where the development of unusual understandings from the general habit or what is termed liberal. The terminology of the word means free to make individuals perform actions resolutely without curbing their ability to express themselves. Departing from these roots, this research seeks to fully describe liberalism in the body of Islamic education historically, its role, and its impact on education. The research design used is qualitative with a literature review method through data collection tools consisting of books, journals, proceedings, reports, and papers as primary data as well as the use of credible internet sources and documentation of efforts to analyze them. While analyzing the data using descriptive argumentative analysis. The research findiThe background of this research is the unrest that occurs in the Islamic education system where the development of unusual understandings from the general habit or what is termed liberal. The terminology of the word means free to make individuals perform actions resolutely without curbing their ability to express themselves. Departing from these roots, this research seeks to fully describe liberalism in the body of Islamic education historically, its role, and its impact on education. The research design used is qualitative with a literature review method through data collection tools consisting of books, journals, proceedings, reports, and papers as primary data as well as the use of credible internet sources and documentation of efforts to analyze them. While analyzing the data using descriptive argumentative analysis. The research The background of this research is the unrest that occurs in the Islamic education system where the development of unusual understandings from the general habit or what is termed liberal. The terminology of the word means free to make individuals perform actions resolutely without curbing their ability to express themselves. Departing from these roots, this research seeks to fully describe liberalism in the body of Islamic education historically, its role, and its impact on education. The research design used is qualitative with a literature review method through data collection tools consisting of books, journals, proceedings, reports, and papers as primary data as well as the use of credible internet sources and documentation of efforts to analyze them. While analyzing the data using descriptive argumentative analysis. The research findings explain that liberalism in Islamic education has positive and negative meanings. On the positive side, the existence of liberalism breaks the old ways and thoughts that education has been carried out only limited to reading and writing, but more broadly the effort to produce innovative works through critical reasoning as a result of liberal thinking. Then the emergence of methods, materials, and perspectives between educators and students that are no longer restrictive but cause novelty and freshness for practical learning. In addition to the positive impact, the negative side also emerges, namely the existence of a permissive attitude that tends to violate the norms of religious teachings because everything relies on limited logic. explain that liberalism in Islamic education has positive and negative meanings. On the positive side, the existence of liberalism breaks the old ways and thoughts that education has been carried out only limited to reading and writing, but more broadly the effort to produce innovative works through critical reasoning as a result of liberal thinking. Then the emergence of methods, materials, and perspectives between educators and students that are no longer restrictive but cause novelty and freshness for practical learning. In addition to the positive impact, the negative side also emerges, namely the existence of a permissive attitude that tends to violate the norms of religious teachings because everything relies on limited logic.ngs explain that liberalism in Islamic education has positive and negative meanings. On the positive side, the existence of liberalism breaks the old ways and thoughts that education has been carried out only limited to reading and writing, but more broadly the effort to produce innovative works through critical reasoning as a result of liberal thinking. Then the emergence of methods, materials, and perspectives between educators and students that are no longer restrictive but cause novelty and freshness for practical learning. In addition to the positive impact, the negative side also emerges, namely the existence of a permissive attitude that tends to violate the norms of religious teachings because everything relies on limited logic.